2020
DOI: 10.1093/ajcn/nqaa055
|View full text |Cite
|
Sign up to set email alerts
|

Maternal glycemia during pregnancy and offspring abdominal adiposity measured by MRI in the neonatal period and preschool years: The Growing Up in Singapore Towards healthy Outcomes (GUSTO) prospective mother–offspring birth cohort study

Abstract: ABSTRACT Background Gestational diabetes is associated with unfavorable body fat distribution in offspring. However, less is known about the effects across the range of maternal gestational glycemia on offspring abdominal adiposity (AA) in infancy and early childhood. Objectives Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…It is not immediately clear why elevated FPG, but not 2hPG, is associated with early cessation of breastfeeding. A possible reason lies in the different pathophysiological mechanisms underlying FPG vs 2hPG which result in different metabolic abnormalities (18,19); this is supported by data from our cohort as FPG appears to exert a greater and more sustained influence on child growth and adiposity than 2hPG (21,49). We are unaware of other studies that have examined the association of FPG and breastfeeding duration.…”
Section: Discussionsupporting
confidence: 58%
“…It is not immediately clear why elevated FPG, but not 2hPG, is associated with early cessation of breastfeeding. A possible reason lies in the different pathophysiological mechanisms underlying FPG vs 2hPG which result in different metabolic abnormalities (18,19); this is supported by data from our cohort as FPG appears to exert a greater and more sustained influence on child growth and adiposity than 2hPG (21,49). We are unaware of other studies that have examined the association of FPG and breastfeeding duration.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast with prior exposure to higher maternal fasting glycemia myo-inositol treatment generally increased 13 C-AA phospholipids (dots above y =0) ( Figure 4 , column 2). The association crossed the x axis around a fasting glycemia level of 4.4–4.5 mM, which is the median concentration in the general obstetric population [ 39 ]. Since endogenous phospholipids were lower with increasing fasting glycemia exposure ( Figure 2 C), this suggests that myo-inositol could act to bring AA-phospholipids towards physiological means, thus moderating AA placental metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…We observed the effects predominantly in males. European studies have reported increased adiposity in both sexes or restricted to males [27] . It would be interesting to explore the sex differences further.…”
Section: Discussionmentioning
confidence: 99%
“…The only comparable Indian follow up study (the Parthenon Cohort) made serial anthropometric measurements in ODM and ONDM and found that the offspring of diabetic mothers weighed more at birth, with a 'catch-down' in infancy and a rebound in early childhood, especially in girls (13,14). In contrast, European studies have reported increased adiposity in both sexes or restricted to boys (29). It would be interesting to explore this further.…”
Section: Salient Findingsmentioning
confidence: 99%